Which form of venture capital is most supportive of innovation? - Fabio Bertoni; Tereza Tykvová (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Although there seems to be consensus in the literature that venture capital investors increase the innovation output of their portfolio companies, there is little evidence about how investor type (governmental vs. private) and transaction structure (syndicated vs. non-syndicated) moderate this impact. Using a sample of 865 young biotech and pharmaceutical companies from seven European countries, we investigate which form of venture capital is most supportive of innovation. Our results suggest that in companies financed by syndicates and by private venture capital investors, the innovation output increases significantly faster than in non-venture-backed companies. The most supportive form is a heterogeneous syndicate (i.e., consisting of both types of venture capital investors) led by a private investor.
Keywords: G24; H0; O3; 330; innovation; patents; private venture capital investors; governmental venture capital investors; syndication; biotech and pharmaceutical companies; Europe